Z zagadnień analizy i prognoz ludności zawodowo czynnej - Breznik, Dušan (Wydział Prawa i Administracji UAM, 1968)
The numerical relation of people economically active to the whole population is influenced by many factors which can be differentiated into: demographic, social and economic. To the first group, among others, belong the structure of population according to sex;, age and civilian status, level of fertility and mortality and intensity of the immigration movement. Important among social factors are the relations and conditions of commencement and conclusion of economical activity: years at school, resignation from work of employed women, health, invalidism, absency and the pension system.. By applying the correlation calculation and regression equation it is possible to investigate the impact power of the factors enumerated on the level of economical activity. Such investigations should be conducted separately for both sexes. During examinations of men in Yugoslavia, 20 districts were differentiated and three different explanations taken into account: percentage of men economically active in relation to the male population, percentage of men economically active in agriculture, percentages of country youth in the ages of 15—19 in relation to all the youth of this age. The multiple correlation coefficient obtained was R=0,97. Investigation of the level and factors shaping he level of economical activity facilitates a prognosis of the number of population economically active. Among the many methods predicting this population of great significance are: the analytical method based on a hypothesis of fertility, mortality and migration; mathematical method constituting extrapolation, the graph of transient changes in economically active population, methods utilizing data of factors influencing the level of economical activity, including the regression method.
On the Problems of Analysis and Prognosis of a Population Economically Active